Pushes and Pulls of ISO28000 Implementation in Supply-Chain of Malaysia Mining - Chong Yee Chin; Wong Huei Ing; Shahryar Sorooshian; Muzamir Hassan (International Journal of Supply Chain Management, 2019)
Supply chain security is one of the components of an industry’s strategy to protect their chain from any risk that can damage their supply chain. ISO 28000 is a standard which specify requirement for security management system for the supply chain. However, there are still many organizations didn’t apply for this standard. Still many mining industries are doubtful about the effectiveness of ISO 28000. This paper objective to examine the pushes and pulls of ISO 28000 implementation for Pahang mining industry. From literature, potential pushes and pulls are identified, then the researchers undergo interview session with experts in mining industry from Pahang of Malaysia. Based on the interview result, this study introduces a list of pushes and pulls to the supply chain security standard. This contributes to implementation of ISO 28000 in mining industry of Malaysia, specifically Pahang. In the industry, the result of this study is beneficial for supply chain managers and policy-makers to ease the ISO implementation and reduce supply chain risks.